Economic damage of grassland spittlebugs (Homoptera Cercopidae) in Colombia: a first approximation of impact on animal production in Brachiaria decumbens - Holmann, Federico J.; Peck, D. (Springer, 2002)
Using a simulation model as an analysis tool, the economic impact of spittlebugs in pastures of Colombia was quantified in terms of animal production. Three levels of abundance (10, 25, 50 adults/m2) and farm area affected (25, 50, 100%) were evaluated using data obtained in Brazil for Notozulia entreriana (Berg) on Brachiaria decumbens Stapf. The model considered dual-purpose production systems in two contrasting ecosystems: (1) the dry tropics, characterized by a well defined, 6-month rainy season and (2) the humid tropics, characterized by uniform rainfall distribution throughout the year. Compared to healthy pastures, stocking rate, milk and meat productivity decreased 1-8, 8-34 and 38-54%, respectively, at low, intermediate and high abundance levels, depending on farm area infested. The cost of producing milk and meat increased 0-4, 3-16 and 18-30% at the same infestation levels, causing net income to decrease 3-16, 17-69 and 67-100%. At the regional level, economic damage in the 1,140,000 ha sown to grasses susceptible to spittlebugs in the humid tropics of Colombia ranged from US$7-25, 28-36 and 39-47 million/yr. In the 4,720,000 ha of susceptible grasses in the dry tropics, economic damage was US$33-118, 132-175 and 228-273 million/yr. The investment required to develop grass varieties resistant to spittlebugs and adapted to soils with low to intermediate fertility (US$6 million over 12 yr) is low compared with the economic damage caused by spittlebugs in Colombia, and therefore presents a major economic incentive for support of research on varietal improvement and spittlebug management.